FUNCTION OF THE HIPPOCAMPUS IN THE PROCESS OF MEMORY AND LEARNING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article analyzes the role of the hippocampus in the process of memory and learning. The hippocampus is an important part of the central nervous system, participating in the formation of short- and long-term memory, encoding and retrieval of information. Studies show that the activity of neurons in the hippocampus regulates the learning process through neuroplasticity and synaptic strengthening. At the same time, stress, sleep disorders and psychological factors can negatively affect hippocampal function. The article discusses the physiological mechanisms of the hippocampus, its role in learning, and ways to reduce its dysfunction on a scientific basis.